EPC Minutes 2004-09-30 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda amended and Approved. Minutes of 1/31/19 Approved. President Report. Provost Report. Vice Chair Report. AVP for Student Affairs Report. Associated Students Report. Statewide Senator Report. Staff Representative Report. Resolution re: President's Climate Leadership Commitment – First Reading. Commencement Update. Discussion of GE reform vote. EPC Report. APARC Report. FSAC Report. SAC Report. CFA Report.